CSC773 - Parallel Computing / College of Computing, Informatics And Media - UiTM, College of Computing, Informatics And Media (Universiti Teknologi MARA (UiTM), 2023)
This course introduces the parallelism fundamentals and parallel algorithm design for improving computational performance. It emphasizes the decomposition and mapping techniques in constructing parallel algorithms. The parallel programming paradigms, namely, the shared address space and message passing are applied to implement parallel programs. Other topics include the analytical modeling and parallel algorithms.